Who gives? - The Roles of Empathy and Impulsiveness - James Andreoni; Ann-Kathrin Koessler; Marta Serra-Garcia (ZBW – Leibniz Information Centre for Economics, 2018)
We investigate the impact of empathy and impulsiveness on charitable giving using a real donation experiment. We confirm that greater empathy predicts greater charitable giving. Contrary to recent literature, however, we find a significant negative relationship between impulsiveness and donation behavior. Specifically, when financial resources are scarce, donations are more often made by decisionmakers who are able to suppress an intuitively egoistic response.
Additional information: Copyright statement: Please note this is a pre-review version of the article published in Scharf, Kimberley, and Mirco Tonin (eds.), The Economics of Philanthropy: Donations and Fundraising, pp. 49-62. 2018 Massachusetts Institute of Technology, courtesy of the MIT Press. http://mitpress.mit.edu/books/economics-philanthropy
Keywords: C91; D64; H40; 330; Charitable Giving; Donation; Empathy; Impulsiveness